Production of No-Carrier Added Lutetium-177 by Irradiation of Enriched Ytterbium-176 - A. Tarasov, Valery; I. Andreev, Oleg; G. Romanov, Evgeny; A. Kuznetsov, Rostislav; V. Kupriyanov, Vladimir; V. Tselishchev, Ivan (Current Radiopharmaceuticals, 2015)
Two methods of Lu-177 production are reviewed: irradiation of isotopically enriched Lu- 176 (direct way) and irradiation of ytterbium enriched with Yb-176 (indirect way). Based on neutronphysical calculations Lu-177 yield and specific activity were estimated for both methods. Lu-177 specific activity strongly depends on neutron flux density in the direct way, that is 75,000 Ci/g for 10- days irradiation in a neutron flux of 2.1015 cm-2s-1, and only 13,000 Ci/g after 30 days irradiation at neutron flux 1.1014 cm-2s-1. Irradiation of Yb-176 provides Lu-177 specific activity close to theoretical value (110,000 Ci/g). Neutron flux density effect Lu-177 yield, that is 530 Ci/g for 2.1015 cm-2s-1 neutron flux density after 30 days irradiation. A procedure of isolation and purification of Lu-177 from irradiated targets is described based on combination of galvanostatic extraction of ytterbium followed by cation-exchange chromatography from alfa-hydroxyisobutirate solutions on BioRad AG®50W-X8 resin.
Keywords: reactor production